The Relation between 'Democracy & Participation' - Subedi, Girdhari (Journal of Political Science, 2004)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Journal of Political Science Vol.7(1) 2004 p.1-4